LITERASI SELOKO ADAT MELAYU JAMBI PADA MASYARAKAT JAMBI - Zulpa Raudhotul Jannah; Sriwahyuni Sriwahyuni; Ella Novitasari; Rustam Rustam; Priyanto Priyanto (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This article discusses the literacy skills of the Jambi Malay Traditional Seloko in the Jambi society. Jambi Malay customary Seloko is a part of Jambi Malay oral literature which contains traditional expressions containing traditional words, proverbs, pantun, admonitions, and figurative words that contain messages and mandates to be conveyed from the Seloko presented. Customary Seloko of Jambi Malay is presented to find out how society can understand and apply the contents of the Jambi Malay Customary Seloko. The analysis of this research uses qualitative with a descriptive approach and data collection through observation and interview methods. The analysis results show that the Jambi society's ability to access information on the Jambi Malay Customary Seloko still needs to be improved. Of the 13 respondents who were asked, there were only two respondents who accessed via the internet, one respondent through books, and ten others through weddings and inauguration of village heads. In evaluation information, Customary Seloko of Jambi Malay was also in a bad state because of the 91 questions asked to the respondents, only 33 questions could be answered well. In contrast, 58 of them were answered incorrectly. At the same time, in terms of the use of information, Customary Seloko of Jambi Malay can be categorized as good because all respondents stated that they always try to actualize the message of Customary Seloko of Jambi Malay in their daily lives.